Amide Proton Transfer-Weighted MRI Might Help Distinguish Amnestic Mild Cognitive Impairment From a Normal Elderly Population - Guo, Zixuan; Jiang, Yanchun; Qin, Xiaoyan; Mu, Ronghua; Meng, Zhuoni; Zhuang, Zeyu; Liu, Fuzhen; Zhu, Xiqi (Frontiers in Neurology, 2021)
Objectives: To evaluate whether 3D Amide proton transfer weighted (APTw) imaging based on magnetization transfer analysis can be used as a novel imaging marker to distinguish amnestic mild cognitive impairment(aMCI) patients from normal elderly population by measuring changes in APTw signal intensity in the hippocampus and amygdala. Materials and Methods: 70 patients with aMCI and 74 healthy volunteers of matched sex and age were recruited for routine MRI sequence and APT imaging examination. Select the bilateral hippocampus and amygdala from two consecutive APT images to measure the magnetic resonance ratio asymmetry (MTRasym) of the amide protons (at 3.5 ppm) in regions of interest, which are defined as APTw values. And compare the difference in APTw values of the bilateral hippocampus and amygdala between aMCI group and the control group. The independent sample t test was used to evaluate the difference in APTw value of the bilateral hippocampus and amygdala between the aMCI group and the control group; The paired t test was used to evaluate the difference between the APTw values of the left hippocampus and amygdala and the right hippocampus and amygdala, both in aMCI group and control group. Result: The APTw of bilateral hippocampus and amygdala in aMCI group was higher than that in control group, and the difference was statistically significant (Left-hippocampus 1.01vs. 0.77% P﹤0.001；Right-hippocampus 1.02vs. 0.74%, P﹤0.001；Left- amygdala 0.98vs. 0.70% P﹤0.001；Right- amygdala 0.94vs. 0.71%, P﹤0.001). There was no significant difference in APTw values of bilateral hippocampus and amygdala not only in aMCI group but also in control group (aMCI group Left-hippocampus 1.01 vs. Right-hippocampus 1.02%, P=0.652；healthy control group Left-hippocampus 0.77 vs. Right-hippocampus 0.74%, P=0.314; aMCI group Left- amygdala 0.98 vs. Right- amygdala 0.94%, P=0.171; healthy control group Left- amygdala 0.70 vs. Right- amygdala 0.71%, P=0.726). Conclusion: APTw can be used as a new imaging marker to distinguish aMCI patients from normal elderly population by indirectly reflecting the changes of protein content in hippocampus and amygdala.